Mining of the pyrrolamide antibiotics analogs in Streptomyces netropsis reveals the amidohydrolase-dependent "iterative strategy" underlying the pyrrole polymerization. - Chunlin Hao (Public Library of Science (PLoS), 2014)
In biosynthesis of natural products, potential intermediates or analogs of a particular compound in the crude extracts are commonly overlooked in routine assays due to their low concentration, limited structural information, or because of their insignificant bio-activities. This may lead into an incomplete and even an incorrect biosynthetic pathway for the target molecule. Here we applied multiple compound mining approaches, including genome scanning and precursor ion scan-directed mass spectrometry, to identify potential pyrrolamide compounds in the fermentation culture of Streptomyces netropsis. Several novel congocidine and distamycin analogs were thus detected and characterized. A more reasonable route for the biosynthesis of pyrrolamides was proposed based on the structures of these newly discovered compounds, as well as the functional characterization of several key biosynthetic genes of pyrrolamides. Collectively, our results implied an unusual "iterative strategy" underlying the pyrrole polymerization in the biosynthesis of pyrrolamide antibiotics.